2013
DOI: 10.1111/bjh.12682
|View full text |Cite
|
Sign up to set email alerts
|

Secrets of platelet exocytosis – what do we really know about platelet secretion mechanisms?

Abstract: Upon activation by extracellular matrix components or soluble agonists, platelets release in excess of 300 active molecules from intracellular granules. Those factors can both activate further platelets and mediate a range of responses in other cells. The complex microenvironment of a growing thrombus, as well as platelets' roles in both physiological and pathological processes, require platelet secretion to be highly spatially and temporally regulated to ensure appropriate responses to a range of stimuli. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 117 publications
0
41
0
2
Order By: Relevance
“…Upon activation by extracellular matrix components or soluble agonists, platelet α-granules release hundreds of different types of active molecules, which further activate platelets and thus participate in a series of responses to aggravate the inflammatory damage in sepsis. Platelet α-granule contents include coagulation proteins (e.g., fibrinogen), protease inhibitors (e.g., plasminogen activator inhibitor-1), growth factors (e.g., PDGF), soluble adhesion molecules (e.g., vWF), and membrane adhesion molecules (e.g., P-selectin) [11]. Platelet α-granule heterogeneity and differential release possibly account for opposing actions of physiological and pathological correlates in sepsis [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon activation by extracellular matrix components or soluble agonists, platelet α-granules release hundreds of different types of active molecules, which further activate platelets and thus participate in a series of responses to aggravate the inflammatory damage in sepsis. Platelet α-granule contents include coagulation proteins (e.g., fibrinogen), protease inhibitors (e.g., plasminogen activator inhibitor-1), growth factors (e.g., PDGF), soluble adhesion molecules (e.g., vWF), and membrane adhesion molecules (e.g., P-selectin) [11]. Platelet α-granule heterogeneity and differential release possibly account for opposing actions of physiological and pathological correlates in sepsis [37].…”
Section: Discussionmentioning
confidence: 99%
“…It have been identified that SNAREs and SNARE accessory proteins control the process of α-granule secretion [11,35]. Known VAMP8, syntaxin2 and SNAP23 are highlighted by reports showing enrichment at sites of platelet membrane fusion [36].…”
Section: Corm-2 Regulates Snares Complex Assembly In Lps-stimulated Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The most well-characterized aspects of platelets are the roles they play in hemostasis and thrombosis, but they have also been implicated in processes such as inflammation and the migration of cancer cells [1-3]. …”
Section: Introductionmentioning
confidence: 99%
“…Platelets store cargo in granular stores called α-granules (alpha granules), δ-granules (dense granules) and lysosomal granules, containing different sets of hemostatically active ingredients that are released upon activation by a calcium-dependent exocytotic mechanism (Golebiewska and Poole, 2013). As the physiological relevance of lysosomal release is currently unclear, only dense granules and alpha granules will be described in this section.…”
Section: Granule Releasementioning
confidence: 99%